Determination of histamine in fish and fish products: validation of photometric method (Environment & Health, 2022)
Topicality: The content of histamine in high concentrations causes a number of diseases that even lead to death, it is one of the indicators that characterizes the safety of fish and fish products. Therefore, the choice or development of a simple and inexpensive method for the determination of histamine content in fish and fish products is relevant.Objective: We confirmed the effectiveness of photometric method for the determination of histamine in fish and fish products by obtaining and analyzing validation characteristics.Results: Based on the results of validation, it has been substantiated and experimentally proved that the photometric method of quantitative determination of histamine can be correctly reproduced and is suitable for the quality control of measurements. The most acceptable results were obtained for histamine concentrations in the range from 50.0 ± 0.1 to 200.0 ± 0.5 mg/kg. The lower histamine concentrations are characterized by a higher percentage of total uncertainty, although it is also within acceptable values.Conclusions: Evaluation of the obtained validation characteristics indicates that this technique can be used to quantify the content of histamine in fish and fish products and is not inferior in accuracy and correctness to the method of high performance liquid chromatography.
Keywords: histamine; decarboxylation; biogenic amine; photometric method; validation; convergence; reproducibility